The Existing Curriculum and Teaching Learning Challenges for Prevention and Handling Sexual Violence in Higher Education - Sartiah Yusran; Trias Setiawati (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Sexual Violence (SV) has been increased in universities and victims have more silence due to fear and shame. There is no clear mechanism in protecting the rights of victims. This study aims to analyze the problems of SV on campus, to examine the existing curriculum and its challenge in integrating the concept of SV. This is a collaborative research between the University of Halu Oleo Kendari, the University of Islam Indonesia Jogyakarta and the University of Syah Kuala Banda Aceh. The study applied a mixed method of quantitative and qualitative using surveys, In-depth interviews and FGDs and analyzed using triangulation. Total respondents 435 for survey and 34 for 3 FGD and 4 key informants for In-depth interview, and were representative for students, lecturer and staff applying Stratified Purposive Random Sampling. The results showed that respondents reported ever experienced at least once sexual harassment in their life either perpetrated by someone they knew or stranger. 79.31% respondents claimed their friends as victims and 36.78% recognized their friends as perpetrators, while 14.94% respondents claimed themselves as the victims. The underline problem of SV that occurs on campus is due to a very strong patriarchal culture in the concext of power relationship and gender inequality. These have been recognized as a trigger for the high number of SV cases on campus. In addition, the existing curriculum identified some topics related to prevention and response the case of SV, however, they were recognized as hidden curriculum. The challenges were political commitment due to unwanted sexual attention and gender violence were the two mostly do not reported as the form of SV. Therefore, there is an urgent need to re-define the concept of SV in actual curriculum, instead of being a hidden curriculum.